Physical activity and sedentary time in a rural adult population in Malawi compared with an age-matched US urban population. Issue 1 (12th October 2020) - Pratt, Michael; Sallis, James F; Cain, Kelli L; Conway, Terry L; Palacios-Lopez, Amparo; Zezza, Alberto; Spoon, Chad; Geremia, Carrie M; Gaddis, Isis; Amankwah, Akuffo; Friedman, Jed; Kilic, Talip
Abstract : Objectives: This study was designed to assess patterns of objectively measured physical activity (PA) and sedentary behaviour in a sample of adults in a rural setting from a low-income Sub-Saharan African country (Malawi). The patterns of PA and sedentary behaviour in Malawi were compared with US data collected and analysed using the same methodology. Methods: The Malawi PA data were collected as part of a survey experiment on the measurement of agricultural labor conducted under the World Bank Living Standards Measurement Study program. ActiGraph accelerometers (model GT3X) were worn on the right hip in a household-based sample of 414 working-age adults (15–85 years). Results: Mean total and 95% CIs for PA by category in min/day for Malawi adults were: sedentary 387.6 (377.4–397.8), low-light 222.1 (214.7–229.5), high-light 136.3 (132.7–139.9), moderate 71.6 (68.8–74.5), vigorous 1.1 (0.5–1.8) and moderate-to-vigorous physical activity (MVPA) 72.8 (69.7–75.9). Mean of PA and sedentary behavior (min/day) summed across age and sex groups are compared between Malawi and US samples: sedentary behaviour, 387.6 vs 525.8 (p<0.001); low-light, 222.1 vs 217.0 (p=ns); high-light, 136.3 vs 45.6 (p<0.001); moderate, 71.6 vs 28.0 (p<0.001); vigorous, 1.1 vs 2.5 (p<0.001); MVPA, 72.8 vs 30.5 (p<0.001). Compared with the USA, Malawi participants averaged consistently less sedentary time/day and more minutes/day in all intensity levels of PA, except for low-light and vigorous PA. Conclusion: Overall, levels of MVPA and high-light activity in adults in Malawi were substantially higher and sedentary time was substantially lower than those observed in US samples using near identical data collection, scoring and analysis.